Hypercaloric Diet Establishes Erectile Dysfunction in Rat: Mechanisms Underlying the Endothelial Damage - de Souza, Iara L. L.; Barros, Bárbara C.; de Oliveira, Giuliana A.; Queiroga, Fernando R.; Toscano, Lydiane T.; Silva, Alexandre S.; Silva, Patrícia M.; Interaminense, Leylliane F. L.; Cavalcante, Fabiana de Andrade; da Silva, Bagnólia A. (Frontiers in Physiology, 2017)
Obesity is characterized by an excessive increase in body mass, leading to endothelial damage that may favor the development of erectile dysfunction (ED). ED is defined as the inability to achieve or maintain a penile erection long enough to have a sexual intercourse. In this context, different ED models were developed, however the high price of special animals or the long period to establish the disease has limited studies in this field. Therefore, this study proposed to establish and characterize a novel model of ED in rats associated to a hypercaloric diet consumption. Animals were randomly divided into control group (CG), which received a standard diet, and obese group (OG), fed with a hypercaloric diet during 8 weeks. Rat’s erectile function was evaluated in vivo and in vitro. Food and caloric intake of OG were reduced compared to CG, due to an increased diet energy efficiency. However, OG presented an increased body mass, inguinal, retroperitoneal and epididymal adipose tissues, as well as body adiposity index at the end of experimental protocol. In erectile function analysis, there was a decrease in the number and the latency of penile erections in OG. Additionally, the contractile reactivity of corpus cavernosum was increased in OG, favoring penile detumescence and related to a reduced nitric oxide bioavailability and an increased in contractile prostaglandins levels as a consequence of endothelial damage. Moreover, the endothelium relaxation reactivity of corpus cavernosum was attenuated in OG associated to the oxidative stress. Thus, it was provided a model for advances in sexual dysfunction field and drug discovery for ED treatment.